2000
DOI: 10.3354/dao040195
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyophonus-like infection in wild amphibians from Québec, Canada

Abstract: ABSTRACT. Myositis associated with infection by Ichthyophonus-like organisms was diagnosed in 35 of 260 (13%) wild amphibians collected in Quebec, Canada, from 1959 to 1964 , and 1992 to 1999 (n = 230). Infection was diagnosed in 17 green frogs Rana clamitans, 9 wood frogs R, sylvatica, 4 red-spotted newts hrotophthalmus viridescens, 3 bullfrogs R. catesbeiana, 1 spring peeper Pseudacris crucifer, and 1 pickerel frog R. palustris. The spring peeper and one of the bullfrogs were collected in 1964 from the Mont … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…The lesions were consistent with those described elsewhere for Ichthyophonus in amphibians (Herman, 1984;Mikaelian et al, 2000) and ranged from small, typically longitudinally arrayed discrete nodules to larger swellings that involved more than 50% of the length of the animal (see below). Herman (1984) reported that newts in apparently advanced stages of Ichthyophonus infection exhibited ulcerated lesions that had been secondarily invaded by bacteria.…”
Section: Methodssupporting
confidence: 67%
See 3 more Smart Citations
“…The lesions were consistent with those described elsewhere for Ichthyophonus in amphibians (Herman, 1984;Mikaelian et al, 2000) and ranged from small, typically longitudinally arrayed discrete nodules to larger swellings that involved more than 50% of the length of the animal (see below). Herman (1984) reported that newts in apparently advanced stages of Ichthyophonus infection exhibited ulcerated lesions that had been secondarily invaded by bacteria.…”
Section: Methodssupporting
confidence: 67%
“…The cause of the lesions was identified by the National Wildlife Health Center in Madison, Wisconsin, as an Icthyophonus-like fungus. My own observations and those of others (Herman, 1984;Mikaelian et al, 2000;Green et al, 2002) suggest that the Ichthyophonus-like organism may have been an endemic pathogen in newts for some time, only now becoming more prevalent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Ichthyophonosis appears to be enzootic in Quebec, Canada, where a variety of frogs and one redspotted newt displayed infection with this organism (Mikaelian et al, 2000). To our knowledge, this is the first report of the infection of adult Ambystoma maculata by Ichthyophonus-like organisms in Virginia.…”
mentioning
confidence: 78%